One forgotten name, and another misinterpreted, in Lomariocycas (Blechnaceae, Polypodiopsida) - Vicent, Maria; Gabriel Y Galan, Jose Maria; Molino, Sonia (Phytotaxa, 2018)
Blechnaceae Newman (1844: 8) is a subcosmopolitan family of leptosporangiate ferns (Polypodiopsida), which comprises around 250 species (Pteridophyte Phylogeny Group 2016). Until recently, most of this diversity fell under one, large genus Blechnum Linnaeus (1753: 1077), but after the accumulation of strong evidence of its non-monophyletic status (Shepherd et al. 2007, Gabriel y Galán et al. 2013, Perrie et al. 2014, Gasper et al. 2017), it was split into several entities. Thus, in its current conception, Blechnaceae is formed by 24 genera (Pteridophte Phylogeny Group 2016).